From Dumpster to Dicta: How the BALCO Investigation Created Incurable Violations of Players’ Rights and How to Prevent Them - Ikegami, Bryan T. (The Columbia Journal of Law & the Arts, 2011)
Baseball is widely regarded as America’s pastime. With that designation comes certain expectations from the American public about the integrity of the game. Major League Baseball (“MLB”) has faced challenges to that integrity in the past, including gambling and drug use, but its response has generally been timely and adequate. To the extent these controversies involved illegal activity, the government has stepped in accordingly. Presently, the sport is mired in a well documented controversy regarding player use of performance enhancing drugs. By and large, the government has not had to police the league itself. This time, however, MLB’s response was slow and insufficient. As a result, each branch of the government got involved. President George W. Bush directly addressed the issue in his State of the Union Address on January 20, 2004, calling on “team owners, union representatives, coaches and players to take the lead, to send the right signal, to get tough and to get rid of steroids now.” On March 17–18, 2005, six players and four executives testified before the House Committee on Government Reform regarding drug use inbaseball. During that same year, members of Congress introduced at least three bills aimed at curbing the drug problem in professional sports. Each bill required all players in the four major professional sports leagues to submit to mandatory uniform testing for performance enhancing drugs (“PEDs”). Meanwhile, federal investigators began targeting an illegal drug ring in Northern California, which subsequently ballooned into protracted litigation. The origin and resolution of United States v. Comprehensive Drug Testing, Inc. is the primary focus of this Note.